2017
DOI: 10.1016/j.molmed.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Modifiers of GRN -Associated Frontotemporal Lobar Degeneration

Abstract: Heterozygous loss-of-function (LOF) mutations in the human progranulin gene (GRN) cause frontotemporal lobar degeneration (FTLD) by a mechanism of haploinsufficiency. Patients present most frequently with frontotemporal dementia, which is the second most common neurodegenerative dementia at young age. Currently, no disease-modifying therapies are available for these patients. Stimulating GRN protein expression or inhibiting its breakdown is an obvious therapeutic strategy, and is indeed the focus of current pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 163 publications
0
22
0
Order By: Relevance
“…The dosage of circulating progranulin sped up the identification of GRN mutations thus favoring genotype-phenotype correlation studies. In GRN null mutation carriers it has been demonstrated that the shortage of progranulin (i) invariably precedes clinical symptoms, since a reduction of protein is also measured in pre-symptomatic subjects (ii) is associated with multiple clinical presentations ranging from behavioral variant of frontotemporal dementia (bvFTD) (the most common clinical presentation), to primary progressive aphasia, corticobasal syndrome, AD, Parkinson's disease or dementia with Lewy bodies phenotype (Le Ber et al, 2008 ; Benussi et al, 2009 ; Arosio et al, 2013 ; Wauters et al, 2017 ).…”
Section: Loss Of Progranulin In Alzheimer's Disease Frontotemporal Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The dosage of circulating progranulin sped up the identification of GRN mutations thus favoring genotype-phenotype correlation studies. In GRN null mutation carriers it has been demonstrated that the shortage of progranulin (i) invariably precedes clinical symptoms, since a reduction of protein is also measured in pre-symptomatic subjects (ii) is associated with multiple clinical presentations ranging from behavioral variant of frontotemporal dementia (bvFTD) (the most common clinical presentation), to primary progressive aphasia, corticobasal syndrome, AD, Parkinson's disease or dementia with Lewy bodies phenotype (Le Ber et al, 2008 ; Benussi et al, 2009 ; Arosio et al, 2013 ; Wauters et al, 2017 ).…”
Section: Loss Of Progranulin In Alzheimer's Disease Frontotemporal Dmentioning
confidence: 99%
“…In these disorders, monogenic forms due to a mutation in a single gene are described. However, a broad phenotypic expression variability between or even within pedigrees bearing the same mutation was found in many late onset monogenic neurodegenerative diseases (Finckh et al, 2000a ; Binetti et al, 2003 ; Rademakers et al, 2007 ; Ghidoni et al, 2012a ; Wauters et al, 2017 ). As we hypothesized “environmental/unidentified risk factors show an unexpected deterministic tendency to produce sporadic non-genetically determined forms of the disease in the vast majority of cases.…”
Section: Introductionmentioning
confidence: 99%
“…Progranulin is implicated in the pathogenesis of rheumatoid arthritis (RA) and other inflammatory diseases. Moreover, the role of PGRN was demonstrated in neurodegenerative and metabolic disorders . It should be noted that little is known about the pathological mechanisms mediating HA; a role for serum PGRN has yet to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors might be conditioning the appearance of the disease, and supporting this is the fact that some studies have nominated genetic modifiers. 43 In addition, the gene is estimated to have 90% penetrance by an advanced age, leaving a small amount of carriers possibly unaffected. 44 In brief, we believe that this particular mutation is responsible for standard FTD and, when both alleles are affected, for mild adult onset NCL.…”
Section: Partially Misdiagnosed Casesmentioning
confidence: 99%